Aortic annulus eccentricity before and after transcatheter aortic valve implantation: Comparison of balloon-expandable and self-expanding prostheses - Schuhbaeck, Annika; Weingartner, Christina; Schmid, Jasmin; Pflederer, Tobias; Rixe, Johannes; Nef, Holger; Schneider, Christian; Lell, Michael; Uder, Michael; Ensminger, Stephan; Feyrer, Richard; Weyand, Michael; et al. (European Journal of Radiology, 2015)
The geometry of the aortic annulus and implanted transcatheter aortic valve prosthesis might influence valve function. We investigated the influence of valve type and aortic valve calcification on post-implant geometry of catheter-based aortic valve prostheses.Eighty consecutive patients with severe aortic valve stenosis (mean age 82 ± 6 years) underwent computed tomography before and after TAVI. Aortic annulus diameters were determined. Influence of prosthesis type and degree of aortic valve calcification on post-implant eccentricity were analysed.Aortic annulus eccentricity was reduced in patients after TAVI (0.21 ± 0.06 vs. 0.08 ± 0.06, p<0.0001). Post-TAVI eccentricity was significantly lower in 65 patients following implantation of a balloon-expandable prosthesis as compared to 15 patients who received a self-expanding prosthesis (0.06 ± 0.05 vs. 0.15 ± 0.07, p<0.0001), even though the extent of aortic valve calcification was not different. After TAVI, patients with a higher calcium amount retained a significantly higher eccentricity compared to patients with lower amounts of calcium.Patients undergoing TAVI with a balloon-expandable prosthesis show a more circular shape of the implanted prosthesis as compared to patients with a self-expanding prosthesis. Eccentricity of the deployed prosthesis is affected by the extent of aortic valve calcification.
EVALuna2:12030